Association between the systemic immuno-inflammation index and hearing loss: result from NHANES 2009–2018 - Zhou, Tingfeng; Mao, Jiesheng; Zhu, Pei; Yu, Xinru; Yang, Xiaokai (Frontiers in Neurology, 2024)
Background: A novel inflammatory marker that measures the degree of systemic immunoinflammation, the systemic immunoinflammatory index (SII) is frequently used to forecast a number of illnesses. According to earlier studies, inflammation may play a role in the pathophysiology of hearing loss (HL).Methods: A sample from the National Health and Nutrition Examination Survey (NHANES) covering the years 2009 to 2018 was used in the current cross-sectional survey. Subgroup analysis and weighted multiple linear regression models were used to examine the independent linear correlation between SII and HL. Fitted smoothed curve analyses were also conducted to show the non-linear relationship between the two variables.Results: Among the 8535 participants, the mean age was 40.92 ± 18.6 years, with 49.01% being male. Notably, individuals with hearing loss demonstrated an SII of 530.00 ± 320.72, while those with normal hearing displayed an SII of 491.21 ± 265.15. The mean ± SD values of low-frequency, speech-frequency, and high-frequency Pure Tone Average (PTA) hearing thresholds were 10. 33 ± 9.79, 12.20 ± 11.11, and 22.48 ± 19.49 dB, respectively. A positive dose-response relationship between higher SII and hearing thresholds was observed after adjusting for potential confounders. Furthermore, the interaction analysis did not reveal any significant impact on this positive correlation.